Análise organizacional da PETROBRÁS - Lemos, Marcelo Scofield de (2001)
This present work is intended to analyze Petrobras at its contextual dimensions verifying the organization model (or role) adopted, and consequently analyzing if the organizational structure is congruent or incongruent to its context in which it is used. The revision of the literature intends to clarify key concepts such as: organization, bureaucratic organization, organic organization, organizational environment, strategy, technology and structure which will be the basis to answer the principal question: Is the organizational structure of Petrobras congruent to its organizational reality?